Hyperspectral x-ray imaging mapping capabilities for nuclear forensics - Carpenter, Matthew H.; Stark, Emily N.; McNeel, Daniel G.; Dede, Stefania; Godt, Christopher J.; Kurtz, Eli S. R.; Jackson, Daniel E.; Tenner, Travis J.; Naes, Benjamin E.; Wurth, Kimberly N.; Wagner, Gregory L.; Croce, Mark P. (Frontiers in Nuclear Engineering, 2025)
Nuclear forensics relies on the integration of complementary signatures to constrain the origins and history of materials. Outcomes benefit from the timeliness and precision of the disparate methods that form typical analysis chains. Sample forms are often either minute in quantity or contain signatures like morphology or composition heterogeneity encoded on a microscale, so many analysis techniques focus on resolving signatures on ever-smaller length scales. The new hyperspectral x-ray imaging (HXI) instrument developed at Los Alamos National Laboratory seeks to improve the information available from scanning electron microscopy (SEM) x-ray spectrum analysis through superior spectral energy resolution vs. typical energy dispersive spectroscopy (EDS) systems in common use in nuclear forensics and other microanalysis fields. Based on arrays of transition-edge sensor (TES) microcalorimeter detectors, this instrument achieves a typical energy resolution of 7 eV full-width at half-maximum (FWHM) at 2 keV, opening new possibilities in trace element detection/analysis and chemical state determination through spectral shape shifts. We present here some of the first applications of the HXI instrument to actinide samples and discuss potential maturation of this nascent technology for future analysis pipelines.